Cryogenic Electron Microscopy for Resolving DNA Nanostructures and Their Complexes. Issue 10 (28th July 2021) - Pan, Muchen; Shi, Jiye; Wang, Lihua; Fan, Chunhai; Liu, Xiaoguo
Abstract : Cryogenic electron microscopy (cryo‐EM) reconstructs 3D morphologies of nanoparticles from tens of thousands of their 2D projection images, revealing the in situ morphologies. Cryo‐EM is a widely used technique for precise structure determination in the field of biology, material science, and chemistry. In the past decades, cryo‐EM has drawn growing attention in DNA nanotechnology, which uses DNA strands as self‐assembly building blocks to construct various uniform DNA nanostructures ranging from several to hundreds of nanometers. DNA nanotechnology allows one to create complex yet programmable architecture. At early stage, only gel electrophoresis is used to evaluate the successful folding of DNA nanostructures, judging from their diverse migration rates. Thereafter, atomic force microscopy (AFM) and conventional transmission electron microscopy (TEM) become two of the most widely adopted techniques; however, they only provide sample surface or projection information. To better understand and guide the design of DNA nanostructures, the demand for characterization of sufficient structural information increases rapidly, which cryo‐EM can satisfy. Herein, typical 3D DNA‐assembly structures are collected, and the workflow of the cryo‐EM technique on these structures is illustrated, and how cryo‐EM improves structural characterization and guides the design optimization of DNA nanostructures is summarized. Abstract : The progress in cryogenic electron microscopy (cryo‐EM) single particle analysis of DNA nanostructures and their complexes is summarized and discussed chronologically. The improvements of data processing methods are emphasized. The essential elements that affect the resolution are also shown. In the end, the challenges and potential applications of this direction are presented.